FUNCTIONALITY OF MICROBIOTA IN PATHOLOGY - Perederii, N.A. (World of Medicine and Biology, 2017)
Resume: In the article the attempt of finding out new scientific methods is carried out for the determination of the essence of the phenomenon of caries and periodontitis.Modeling of natural type led Miller to the creation of chemico-parasitic theory, it was continued in the middle of the twentieth century on the laboratory rodents. It is now considered that it was the most convincing proof of participation of microorganisms in the origin of dental caries.Presently generally accepted, that caries is the acid demineralization of hard tissues of tooth, that arises up as a result of the fermentation of easy digested carbohydrates by the microflora of dental plague at subzero resistance of the enamel.Not all researchers agree with it. There are other opinions. Also not everyone agrees with the thesis that the demineralization arises up because of lowering of рН.According to modern presentations a permanent microbiota of the dental plague is also the reason of origin of inflammatory diseases of paradontium.In the nineteenth century an anthropologist Dubois on the basis of study of plenty of human remains of different epochs defined that the representatives of humanity prone to the disease a periodontitis are steady to the caries. And vice versa - prone to the caries humans are steady to the disease a generalized periodontitis. Since the middle of the twentieth century it has stopped to be observed among people. Now it is possible to find out in a man two these pathologies together.Researches of the last time set that symbiotic mutual relations between a host and microbiota are envisaged by nature in the normal condition. Thus a microbiota is integrated in homoeostasis, physiology, metabolism and immune answer of the host. It is also supposed, that a disease with its characteristic clinical displays is not a necessary link in the biological cycle of the population of pathogenic bacteria. There are opinions that the macroorganism itself initiates co-operating with microbes.It is concluded that the issue of the role of microorganisms in etiology and pathogenesis of dental diseases remains open. The consideration of functional aspects arising up between the microbiota of the host and the organism itself will help to find the answer. For this aim it is natural to use the methods of research of functions and also biological methods of analysis of symbiotic associations.
Keywords: microorganisms; caries; periodontitis